Decitabine improves MMS-induced retinal photoreceptor cell damage by targeting DNMT3A and DNMT3B - Ji, Yanli; Zhao, Meng; Qiao, Xiaomeng; Peng, Guang-Hua (Frontiers in Molecular Neuroscience, 2023)
Retinitis pigmentosa (RP) is a group of neurodegenerative retinopathies causing blindness due to progressive and irreversible photoreceptor cell death. The alkylating agent methyl methanesulfonate (MMS) can induce selective photoreceptor cell death, which is used to establish RP animal models. MMS induces DNA base damage by adding alkyl groups to DNA, and epigenetic modifications influence DNA damage response. Here, we aimed to explore the relationship between DNA methylation and DNA damage response in dying photoreceptors of RP. The mouse RP model was established by a single intraperitoneal injection of MMS. HE and OCT showed the outer nuclear layer (ONL) was significantly thinner after MMS treatment. ERG showed impaired retinal function. TUNEL assay showed the cell death was mainly located in the ONL. The retinal damage induced by MMS was accompanied by hyperexpression of DNA methyltransferases (DNMT)3A/3B. DNMT inhibitor 5-aza-dC was applied to inhibit the activity of DNMT3A/3B, resulting in the remission of MMS-induced photoreceptor cell damage. The ONL was thicker than that of the control group, and the retinal function was partially restored. This protective effect of 5-aza-dC was associated with the down-regulated expression of DNMT3A/3B. These findings identify a functional role of DNMT3A/3B in MMS-induced photoreceptor cell damage and provide novel evidence to support DNMTs as potential therapeutic targets in retinal degenerative diseases.